PROFIL PENGGUNAAN DAN INFORMASI PEMANFAATAN KHASIAT PRODUK HERBAL PADA TERAPI DEGENENRATIF DI TOKO “X” KOTA CILACAP - Setia Permana, Denih Agus (SAINS INDONESIANA, 2023)
Herbal medicine has been widely known for both curing disease and maintaining body health. Treatment of degenerative diseases still relies on therapy that uses synthetic drugs which are used in the long term, thereby increasing the risk of side effects. The increasing use of herbal medicines in society is because it is believed that herbal medicines have fewer side effects than synthetic medicines. Herbal medicines are available in various dosage forms, the aim of this research is to determine the use of herbal medicines used in the therapy of degenerative diseases at the "X" herbal shop Cilacap. The data collection technique is to use all sales data and buyer information related to the purpose of using herbal medicines. the. The results of the research obtained during 3 months of observation showed an increase in February (121pc). The product that is most popular with the public in treating degenerative diseases is in the form of Gamat capsules. It can be concluded that the total number of products sold at shop "X" to treat degenerative diseases is 21 products with the total number of products sold as degenerative therapy being 327pc. The most common herbal product for degenerative therapy is that it is efficacious for treating cholesterol.